Assessment of statistical stability of steel strip hot-rolling process - Czarski, Andrzej (My University, 2008)
Statistical methods belong to the basic quality tools. Among statistical instruments the statistical process control SPC takes particular place. One of the principal tasks of SPC is monitoring of a process by means of control charts. They are first of all Shewhart's control charts. The aim of investigations was to assess stability of technological process of hot-rolling of steel strip. There were available the results of thickness measurements madę with an X-ray thickness gauge as well as measurements of convexity and wedge shape made with a profile measurement gauge. The assessment of statistical process stability was performed by means of Shewarfs control charts technique. In case of thickness the estimation of capability indices Cp, Cpk and Pp, Ppk have been carried out, in addition.

Metody statystyczne należą do podstawowych narzędzi jakości. Szczególne miejsce wśród tych metod zajmuje statystyczne sterowanie procesem (SPC). Jednym z podstawowych zadań SPC jest monitorowanie procesu za pomocą kart kontrolnych, są to przede wszystkim karty kontrolne Shewharta. Celem badań była ocena stabilności procesu walcowania na gorąco taśmy stalowej ze względu na następujące parametry: grubość, wypukłość, klinowatość. Pomiar grubości przeprowadzono za pomocą gruboś domierza rentgenowskiego, natomiast do pomiarów wypukłości i klinowatości użyto profilomierza. Ocenę statystycznej stabilności procesu przeprowadzono za pomocą techniki kart kontrolnych. W przypadku grubości wyznaczono również współczynniki zdolności procesu Cp, Cpk oraz Pp, Ppk.
Badanie statystycznej stabilności procesu walcowania na gorąco taśmy stalowej
Metallurgy and Foundry Engineering
Keywords: quality management; statistical methods; statistical process control (SPC); zarządzanie jakością; metody statystyczne; control charts; statystyczne sterowanie procesem (SPC); karty kontrolne; process capability analysis; zdolność procesu